The Consideration of Future Consequences Scale Among Malaysian Young Adults: A Psychometric Evaluation - She, Long; Ma, Lan; Khoshnavay Fomani, Fatemeh (Frontiers in Psychology, 2021)
Background: The consideration of future consequences (CFC) determines the extent to which individuals consider the potential future outcomes of their current behaviour. The significance of assessing the CFC scale's validation in different contexts has been acknowledged by the previous studies. While the majority of the studies have been conducted among western countries, no study has been conducted in Malaysia. The aim of the current study was to validity a Malaysian version of the CFC Scale among Malaysian young adults. Methods: The methodological cross-sectional approach was adopted in this study. The study recruited 529 young adults (age range = 25 to 40) who fulfilled the inclusion criteria of the paper survey. Construct validity was assessed using content validity, convergent validity, and discriminant validity. Cronbach’s alpha, McDonald’s omega, and Average Inter-Item Correlation (AIC) were used to assess the scale’s internal consistency. Also, composite reliability (CR) and maximal reliability (MaxR) were used to assess the construct reliability. Measurement invariance was tested across gender. Results: The findings of the exploratory factor analysis indicated that the Malaysian version of the CFC Scale has a two-factor structure (i.e., CFC-Future and CFC-Immediate) with 10-item explaining 61.682% of the total variance. The confirmatory factor analysis supported the two-factor structure of the CFC scale with good construct validity. The internal consistency and composite reliability were acceptable (The Cronbach’s alpha, McDonald’s omega, and CR for CFC-I were .901 (CI95:.881 to 918), .901, and .887 respectively. Also, these parameters for CFC-F were .867 (CI95:.838 to 891), .868, and .867). Also, Strong measurement invariance was found between male and female groups. Conclusion: We found acceptable psychometric evidence for the 10-items two-factors CFC scale use in the context of young adults in Malaysia. The validated instrument can be used in future studies to assess young adults’ CFC tendency and CFC related behaviour in Malaysia.